2019
DOI: 10.14202/vetworld.2019.1434-1440
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activities of toxic isolate of Xestospongia testudinaria sponge

Abstract: Aims:The purposes of this study were to determine the anticancer activity of Xestospongia testudinaria sponge isolate and identify the responsible compounds.Materials and Methods:The metabolites were extracted using methanol maceration at room temperature. The separation and purification of metabolites were performed using fractionation and column chromatography. The toxicity was examined using the brine shrimp lethality assay, and the toxic isolates were tested for anticancer activity against HeLa cells. Gas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 35 publications
0
18
0
3
Order By: Relevance
“…Phytol-inhibited cell proliferation and promoted autophagy in MCF-7 and human gastric adenocarcinoma AGS cells [ 37 ]. Other constituents observed were stigmasterol chemopreventive activity in cancer [ 38 ], Ergost-5-en-3-ol [anti-cancer in gastric, lung, and ovarian cancer [ [39] , [40] , [41] , [42] ]], 3,7,11,15-Tetramethyl-2-hexadecen-1-ol [anti-cancer [ 43 ]], 9-Octadecenoic acid, 1,2,3-propanetriyl ester, (E,E,E)-compound (cytotoxic on human epidermoid larynx carcinoma (Hep-2) cell line) [ 44 ], stigmast-4-en-3-one [anti-cancer effect on the MG-63 cell line [ 45 ]].…”
Section: Discussionmentioning
confidence: 99%
“…Phytol-inhibited cell proliferation and promoted autophagy in MCF-7 and human gastric adenocarcinoma AGS cells [ 37 ]. Other constituents observed were stigmasterol chemopreventive activity in cancer [ 38 ], Ergost-5-en-3-ol [anti-cancer in gastric, lung, and ovarian cancer [ [39] , [40] , [41] , [42] ]], 3,7,11,15-Tetramethyl-2-hexadecen-1-ol [anti-cancer [ 43 ]], 9-Octadecenoic acid, 1,2,3-propanetriyl ester, (E,E,E)-compound (cytotoxic on human epidermoid larynx carcinoma (Hep-2) cell line) [ 44 ], stigmast-4-en-3-one [anti-cancer effect on the MG-63 cell line [ 45 ]].…”
Section: Discussionmentioning
confidence: 99%
“…Benzothiazole is a bicyclic ring system with multiple applications such as anti-diabetic, analgesic, anti-convulsant, anti-inflammatory, anti-malarial, anti-microbial, anti-thelmintic and antitumour activities (Gill et al, 2015). 4,8,12,16-Tetramethylheptadecan-4-olide is a possible source of vitamin E (Rontani et al, 2007), and has antimicrobial activity (Osama et al, 2017) and anti-breast cancer properties, as reported by Swantara et al (2019) in a study investigating the volatile compounds of the sponge Xestospongia testudinaria against HeLa cancer cells. The study demonstrates the significance of 4,8,12,16-Tetramethylheptadecan-4-olide as a possible anticancer drug, which was synthesised in this study by fungal endophytes Aureobasidium pullulans, Paracamarosporium leucadendri, Cladosporium sp., Fusarium sp., Hyalodendriella sp., Penicillium chrysogenum, Penicillium chrysogenum and Talaromyces sp.…”
Section: Comparison Of Volatile Metabolites Harvested In Winter and Summermentioning
confidence: 96%
“…The study demonstrates the significance of 4,8,12,16-Tetramethylheptadecan-4-olide as a possible anticancer drug, which was synthesised in this study by fungal endophytes Aureobasidium pullulans, Paracamarosporium leucadendri, Cladosporium sp., Fusarium sp., Hyalodendriella sp., Penicillium chrysogenum, Penicillium chrysogenum and Talaromyces sp. (Swantara et al, 2019).…”
Section: Comparison Of Volatile Metabolites Harvested In Winter and Summermentioning
confidence: 99%
“…Tercatat hampir 5000 senyawa telah diisolasi dari spons dan berefek sebagai antikanker (Swantara et al, 2019). Salah satu jenis spons yang berpotensi sebagai sumber dari senyawa yang bersifat antikanker adalah spons yang berasal dari genus Xestospongia.…”
Section: Pendahuluanunclassified
“…Ekstrak kloroformnya adalah yang paling toksik dengan Nilai LC50 39,81 ppm. Fraksi yang paling beracun dengan LC50 yaitu 44,67 ppm (<1000 ppm, sehingga dilanjutkan ke uji terhadap sel HeLa sebagai uji antikanker) dengan uji MTT(Microtetrazolium) untuk mengukur proliferasi sel berdasarkanpengurangan garam tetrazolium kuning MTT, yang direduksi menjadi kristal formazan ungu oleh mitokondria (Swantara et al, 2019).…”
Section: Hasil Dan Pembahasan a Potensi Spons Sebagai Antikankerunclassified